RESIDU PUPUK NITROGEN DI LINGKUNGAN PERAIRAN HULU DAERAH ALIRAN SUNGAI TONDANO PROVINSI SULAWESI UTARA - Sofia Wantasen (Environmental Research Center (PPLH) of Udayana University, 2015)
The Nitrogen fertilizer which is not absorbed by plant will be impact to residue in theenvironment. The aim of this study was to assess the residues of nitrogen in the aquaticenvironment up stream of the Tondano Watershed during 2013-2015 (three years). Datacollected by observation of agriculture activity and determination of sampling by usingcomposite sampling method in River Panasen which is paddy irrigation outlet canal upstream of the Tondano Watershed during 2013-2015 (three years), was measurement eachthree month and analysis nitrate, nitrite, ammonia in the Laboratory. Method data analysisare Graphic Method and to compare with standart Goverment PP. No. 82/2001 Class II.Results showed that the nitrogen residue concentration (nitrate, nitrite, ammonia) ataquatic environment in the up stream of Tondano Watershed on the growing season in 2013nitrate concentration: 0,293-0,408 mg/l; nitrite 0,001-0,041 mg/l; ammonia 0,04-0,28 mg/l. in the growing season in 2014 concentration nitrate: 0,184-0,628 mg/l; nitrite 0,020,077mg/l;ammonia0,002-0,13mg/l.inthegrowingseasonin2015concentrationnitrate:0,173-0,585mg/l;nitrite0,001-0,029mg/l; ammonia0,05-0,10mg/l.